Pengembangan Komponen Instrumen Terpadu (Kit) Praktikum Kimia Untuk Kelas XII IPA SMA N 1 Kecamatan Kapur IX - etri meilogis (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2021)
Abstract. Laboratory in school is very important in supporting the learning of chemistry, to prove the theory and concept of chemistry through practicum. Currently, there are still schools that rarely do practicum. Several factors caused it, namely the tools and materials needed were not yet available and teaching time was very limited due to the Covid 19 pandemic. To overcome these problems an interesting teaching aid was needed. One of the teaching aids that can be used by students is a valid and practical chemistry practicum kit. This research uses the type of 4-D development research (define, design, develop, desseminate). The results showed that the validation of the chemistry practicum kit for class XII science that had been designed met the very valid criteria with a percentage of 89.21% and the practicality results from student questionnaires were 86%. Keyword: Chemistry practicum kit, Validity, Practicality